PENGARUH PENGGUNAAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS WEBSITE LIVEWORKSHEET TERHADAP MOTIVASI BELAJAR PENDIDIKAN PANCASILA - Adira Salwa Octavia; Didik Iswahyudi; Yulianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The aim of this study is to determine the extent of the impact of using digital Student Worksheets (LKPD) based on the Liveworksheet website on students’ learning motivation in Pancasila Education. The background of this research is based on the low level of learning motivation among fifth-grade students due to the continued use of printed worksheets and textbooks. The method used is a quantitative quasi-experimental design with a pretest-posttest nonequivalent control group design. The research subjects consisted of two classes: class VA as the control group using conventional worksheets and class VB as the experimental group using Liveworksheet-based LKPD. The classes were selected using a saturated sampling technique, in which all members of the population are used as the sample. The instrument used to collect data was a learning motivation questionnaire administered to students before and after the intervention. Data analysis was carried out using an independent sample t-test with SPSS version 25. The results showed a significant difference in learning motivation between the experimental and control groups, with a significance value of 0.001 (p < 0.05). The use of Liveworksheet digital LKPD had a positive effect on students' engagement, enthusiasm, and active participation. These findings indicate that the implemented learning approach had a positive impact on students’ motivation, where the use of interactive technology-based media can serve as an effective alternative in promoting a higher-quality Pancasila Education learning process.